Impact of IFRS on Deferred Taxes Methodology in the Czech Republic and comparison with IFRS for SMEs - Marcela Žárová (European Financial and Accounting Journal, 2011)
Investigating impact of IFRS on the accounting regulatory system in the Czech Republic, there should be highlighted that IFRS were introduced into the regulatory system gradually as a separate regulatory system for determined group of accounting entities, on the other hand IFRS have had influence on the development of the local accounting rules during last decade. It was awaited by practitioners and academics too, that the process of deferred taxes reform will be finalized by issuing the Decree on accounting for business entities and by the Czech Accounting Standard on deferred taxes. But the reform as for deferred taxes was realized only partially and wasn't adopted a holistic approach of IFRS implementation into local national accounting regulatory system. Based on the criticism of partial implementation of IAS 12 into local accounting rules, this article is focused on comparability of Czech accounting rules for deferred taxes with IFRS for SME. Conclusion from this investigation might become fundamentals for similar European accounting systems to the Czech Republic.
Keywords: M41; 650; IAS 12; Deferred tax; IFRS implementation; IFRS for SMEs